Assessment of solid waste management practices in Ikere local government, Ekiti State - Ajinawo, E. J.; Aribasoye, M. R. (Electronic Journal of Education, Social Economics and Technology, 2023)
The study assessed solid waste management practices in Ikere local government area of Ekiti state. The purpose of the study was to find out of solid waste management practice. The descriptive survey design research was used for the study. The sample size of three hundred (300) respondents was used for the study.  Five (5) quarters was selected for the study. Five (5) streets were selected from each of the quarters. The simple random sampling technique was used to select sixty (60) houses from each quarter. The instrument for the study contained twenty-nine (29) items structured questionnaire adapted from O’Leary (2014).  A test-retest method of reliability was used, using Pearson’s Product Moment Correlation (PPMC). A coefficient of 0.67 was obtained at 0.05 level of significance. Chi-Square (x2) was used to test the hypotheses, at 0.05 alpha level. The finding of the study on burning of refuse as a solid waste management practice revealed that, the Null hypothesis was rejected therefore the result was significant. The researcher recommended that adequate attention must be given to waste management in order to safe guard human health.